2014
DOI: 10.3389/fnhum.2014.00586
|View full text |Cite
|
Sign up to set email alerts
|

Cues, context, and long-term memory: the role of the retrosplenial cortex in spatial cognition

Abstract: Spatial navigation requires memory representations of landmarks and other navigation cues. The retrosplenial cortex (RSC) is anatomically positioned between limbic areas important for memory formation, such as the hippocampus (HPC) and the anterior thalamus, and cortical regions along the dorsal stream known to contribute importantly to long-term spatial representation, such as the posterior parietal cortex. Damage to the RSC severely impairs allocentric representations of the environment, including the abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
130
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(150 citation statements)
references
References 162 publications
(239 reference statements)
10
130
0
1
Order By: Relevance
“…To date, most studies have focused on the involvement of RSC in spatial and contextual memory (for reviews, see Vann et al 2009;Bucci and Robinson 2014;Miller et al 2014;, given the known connectivity between RSC and visuo-spatial cortical regions (van Groen and Wyss 1990, 1992, 2003. Here we extend this work by demonstrating for the first time that manipulations of RSC impair remote memory for discrete auditory cues.…”
Section: Discussionsupporting
confidence: 61%
“…To date, most studies have focused on the involvement of RSC in spatial and contextual memory (for reviews, see Vann et al 2009;Bucci and Robinson 2014;Miller et al 2014;, given the known connectivity between RSC and visuo-spatial cortical regions (van Groen and Wyss 1990, 1992, 2003. Here we extend this work by demonstrating for the first time that manipulations of RSC impair remote memory for discrete auditory cues.…”
Section: Discussionsupporting
confidence: 61%
“…Evidence shows that RSP/PCC encodes contextual information to disambiguate stimuli (Miller, Vedder, Law, & Smith, 2014) and is critically implicated in self-referential processes linked to introspection and recollection (Kim, 2012;Schmitz & Johnson, 2007;Whitfield-Gabrieli et al, 2011), representation of self-knowledge in time (D'Argembeau & Salmon, 2012), and internal subjective decision-making (Johnson et al, 2005). Studies on meta-memory have suggested that confidence assessment during recollection is associated with differential engagement of self-monitoring functions mediated by the default network (Chua, Schacter, & Sperling, 2009), within which the RSC/PCC and precuneus both are key nodes.…”
Section: Discussionmentioning
confidence: 98%
“…There is also extensive experimental evidence that damage to the ATN, beyond the memory impairment, also produces dysfunctions in the retrosplenial cortex (Aggleton, 2008(Aggleton, , 2010 suggesting that functional interactions take place between the two regions. The retrosplenial cortex has received attention recently (Aggleton, 2014;Nelson and Aggleton, 2014), as it is generally considered to play a critical role in spatial and contextual memories, which are often considered examples of the same relational system thought to support episodic memory (Eichenbaum et al, 1999;Miller et al, 2014). Such a "relational" function for the retrosplenial cortex has received experimental support (Hindley et al, 2014a,b).…”
Section: Specific Functions Of the Anterior Thalamusmentioning
confidence: 94%